2004
DOI: 10.1063/1.1690112
|View full text |Cite
|
Sign up to set email alerts
|

On the crystallization of thin films composed of Sb3.6Te with Ge for rewritable data storage

Abstract: This article addresses the crystallization of amorphous Sb 3.6 Te films ͑40 nm thick͒ and 5 at. % Ge containing Sb 3.6 Te films ͑10, 20, and 40 nm thick͒ as studied with transmission electron microcopy using in situ annealing. These materials exhibit growth-dominated crystallization, in contrast to the usual Ge 2 Sb 2 Te 5 that shows nucleation-dominated crystallization. Particularly the crystal-growth velocity in these systems has been measured as a function of temperature from which the activation energy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
72
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 21 publications
10
72
2
1
Order By: Relevance
“…With the crystal expanding the crystal front advances and these newly formed crystal planes are "pushed down", resulting in internal lattice bending. 23 This hypothesis is consistent with the SE measurements performed before and after full crystallization of the STO films where a thickness reduction of ∼15% was recorded upon crystallization. of ∼300 nm and with a decreased thickness compared to the amorphous regions.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…With the crystal expanding the crystal front advances and these newly formed crystal planes are "pushed down", resulting in internal lattice bending. 23 This hypothesis is consistent with the SE measurements performed before and after full crystallization of the STO films where a thickness reduction of ∼15% was recorded upon crystallization. of ∼300 nm and with a decreased thickness compared to the amorphous regions.…”
Section: Resultssupporting
confidence: 88%
“…The internal lattice plane bending is due to stress induced by the amorphous-to-crystalline transformation and film densification. 23,24 In the work of Kooi et al it was proposed that, during crystal growth, new crystal planes nucleate at the top interface and the crystal front is characterized by a thickness profile with the crystallized region being thinner than the surrounding amorphous matrix. With the crystal expanding the crystal front advances and these newly formed crystal planes are "pushed down", resulting in internal lattice bending.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolosov et al, and Kooi et al reported reduced internal bending for higher crystal growth rates. 23,24 This indicates that Sr-rich STO shows a higher nucleation probability as well as an increased crystal growth rate. (Figures 3d and 3h) the average grain size is further decreased and the bending contours related to the transrotational structure are no longer present.…”
Section: Resultsmentioning
confidence: 97%
“…On the basis of what is known on those structures, 6,9-11) the dark narrow and elongated regions of the domains are bending contours. [16][17][18][19] Outside the bending contours the silicide planes bend 6) in a way similar to that sketched in the inset of Fig. 2.…”
mentioning
confidence: 54%